HAK DAN KEWAJIBAN SUAMI ISTRI DALAM RUMAH TANGGA PRESPEKTIF ARIS MUNANDAR: - - Khoiriyah, Fatimah; Irsan (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
The aim of this research states that from Aris Munandar's perspective it is important to know and implement the rights and obligations of husband and wife in the household, because there are 35% of journals which state that divorce often occurs, caused by not knowing the rights and obligations of husband and wife in the household. The method used is a qualitative approach using interpretative analysis, by collecting data from scientific works, books and Aris Munadar's observations. The results of this research show that knowing the rights and obligations of husband and wife is not enough, it is necessary to implement these rights and obligations.